The Conundrum of Septic Shock Imitators in Patients with Hematologic Cancers: Case Presentation and Possible Differential Diagnoses - Giorgio Berlot; Giulia Moratelli; Martina Tarchini; Katiuscia Battaglia; Paolo Grassi; Nadia Zarrillo; Vincenzo Colella; Rossana Bussani (Case Reports in Critical Care)
The authors describe the case of a patient treated with several cycles of chemotherapy due to an advanced stage non-Hodgkin lymphoma. One daafter the last cycle, he was admitted to our Intensive Care Unit with a septic shock-like clinical picture which didn’t respond to the aggressive treatment and the patient died a few hours later. The autoptical findings cast some doubts on the diagnosis, and demonstrated the presence of other factors imitating its symptoms. In this article, the mimickers of septic shock are reviewed and discussed, as some of them require an aggressive immunosuppression instead of the recommended treatment for septic shock.